2021
DOI: 10.1021/acs.langmuir.1c00469
|View full text |Cite
|
Sign up to set email alerts
|

Free-Radical Generation from Bulk Nanobubbles in Aqueous Electrolyte Solutions: ESR Spin-Trap Observation of Microbubble-Treated Water

Abstract: Microbubbles are very fine bubbles that shrink and collapse underwater within several minutes, leading to the generation of free radicals. Electron spin resonance spectroscopy (ESR) confirmed the generation of hydroxyl radicals under strongly acidic conditions. The drastic environmental change caused by the collapse of the microbubbles may trigger radical generation via the dispersion of the elevated chemical potential that had accumulated around the gas–water interface. The present study also confirmed the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 80 publications
0
87
0
4
Order By: Relevance
“…OUFBW was supplied by Nippon Beatty Lease Co., Ltd. Nanosui Company (Tokyo, Japan). It requires electrolytes, including sodium, calcium, magnesium, and potassium to stabilize nanobubbles [19]. Accordingly, OUFBWs were prepared by adding 6 (OUFBW6), 9 (OUFBW9), and 11 (OUFBW11) ppm ozone ultrafine bubbles to water containing electrolytes.…”
Section: Preparation Of Oufbw Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…OUFBW was supplied by Nippon Beatty Lease Co., Ltd. Nanosui Company (Tokyo, Japan). It requires electrolytes, including sodium, calcium, magnesium, and potassium to stabilize nanobubbles [19]. Accordingly, OUFBWs were prepared by adding 6 (OUFBW6), 9 (OUFBW9), and 11 (OUFBW11) ppm ozone ultrafine bubbles to water containing electrolytes.…”
Section: Preparation Of Oufbw Solutionsmentioning
confidence: 99%
“…The ozone concentration of each solution was measured using an ozone meter (AOM-05, Sato Shoji Co., Ltd., Japan) and immediately used for subsequent investigations. Ozone-free electrolyte aqueous solution of OUFBW11, which had the highest ozone concentration among all OUFBWs, was referred to as OFEAS since the electrolyte concentration increases proportionally with the ozone concentration [19]. OFEAS and phosphate buffered saline (PBS; pH 7.2) were used as controls.…”
Section: Preparation Of Oufbw Solutionsmentioning
confidence: 99%
“…The growth of bubbles is due to cavitation, which releases surface energy (Shatalov et al, 2012). It has been experimentally proven that under the action of vibration, nanobubbles are a source of reactive oxygen species (Gudkov et al, 2020;Gudkov et al, 2021;Takahashi et al, 2021). Gudkov et al (2020) showed that the relative rate of formation of hydrogen peroxide in water saturated with atmospheric gases is approximately 0.8 nM/min when exposed to the frequency of 30 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…When the nanobubbles were broken, there was a possibility to produce radicals. Takahashi et al, 2021, reported that •OH was generated from the collapsing microbubbles, including oxygen with 2 vol% ozone in 1 mM FeSO4 aqueous solution under strongly acidic conditions without ultrasound or a large pressure difference [25]. The following Section 3.5 will report and discuss the experimental results on radical observation as a function of solution pH.…”
Section: Number Of Nanobubblesmentioning
confidence: 98%
“…Moreover, the microbubbles on ozonized water indicated the production of •OH by the collapse of the microbubbles [24]. In 2021, they reported that •OH was generated from the collaps-ing microbubbles under strongly acidic conditions without any dynamic stimulus such as ultrasound or a large pressure difference [25]. Liu et al, 2016 reported that •OH and superoxide ion (•O 2 − ) can be produced in an aqueous solution with bulk nanobubbles, and investigated the germination processes for plant seeds [26].…”
Section: Introductionmentioning
confidence: 99%